Electricity Consumption and Food Production in Malaysia: Implication for the Sustainable Development Goal 2 - Osabohien, Romanus; Aderemi, Timothy A.; Jaaffar, Amar Hisham; Oloke, Emmanuel; Bassey, Rowland; Yusoff, Nora Yusma Mohamed; Balogun, Abayomi Stephen; Ifekwem, Nkiruka E. (International Journal of Energy Economics and Policy, 2024)
The need to seek sustainable solutions to end hunger in all its forms by 2030 motivated the implementation of the Sustainable Development Goals. Against this backdrop, this study seeks to fill the existing gap by unraveling the underexplored dimension of escalating electricity consumption and its potential effects on the broader spectrum of Malaysia’s food productivity, with a view to assessing the capacity or otherwise of Malaysia in achieving the SDG 2 (food and nutrition security) by 2030. To achieve the stated objectives, data from World Development Indicators (WDI) of the World Bank for the period 1990 to 2022 were collected for Malaysia. The collated data were analyzed within the framework of Fully Modified Ordinary Least Squares (FMOLS) method. The negative coefficient suggests that an increase in arable land is associated with a decrease in food production. Electricity consumption did not support expansion of food production in the country. Employment in agriculture, based on results, the study concludes that; electricity consumption did not support expansion of food production in Malaysia. In the same vein, arable land in Malaysia did not support sustainable food production in the country. Employment in agriculture did not drive food production changes in the country. Therefore, it could be submitted that electricity consumption only may not ensure a sustainable food production in Malaysia. Therefore, the study recommends that the policymakers and other concerned stakeholders in Malaysia should emphasize the importance of managing and utilizing arable land effectively in order for the country to experience a sustainable food production. Similarly, the policymakers in Malaysia should be given priority to food production when distributing electricity for both domestic and industrial consumptions in the country. If these policies are well implemented in Malaysia, the achievement of the Sustainable Development Goal 2- food security and sustainable agriculture will be tremendously facilitated before 2030.